Pelatihan Home Decoration: Pendant Lamp Dari Mika Film Di Perkumpulan WKRI - Rosalia, Alderina; Rahayu, Elis Sri; Mardika, Kadek (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Home decoration is an activity that is currently very popular, where there are many unique and interesting decorative elements that make the appearance of a house more beautiful.  As part of the aesthetic elements of a room, pendant lamps can also be created yourself using various materials that are easily available on the market. The creative process is very diverse, from the shape and materials used. This time the pendant lamp is made from white mica film, which will make the color of the lamp softer and also the effect of the mica film folds adding to the aesthetics of this lamp. The methods used to empower the target group are: (1) Providing materials, (2) demonstration and practice, and (3) assistance in implementing Home Decoration: Pendant Lamp Training activities at the WKRI (Wanita Katolik Repubik  Indonesia) association, Santa Maria Palangka Raya Branch It is hoped that the results obtained from the activities obtained from the activities of the Community Empowerment Assistant Lecturer Program will be able to express themselves through the practice of craft/handycraft skills, and be able to produce goods that become an expression of themselves and even produce works of art and the members of the association can develop into creative individuals.